Bloodhound on my Trail: Building the Ferranti Argus Process Control Computer - Aylen, Jonathan (The international journal for the history of engineering & technology, 2012)
Digital computers for process control were developed at the end of the 1950s. They had different design objectives from computers for scientific or commercial use. The Ferranti Argus was among the first computers worldwide used for direct digital control. The Argus was invented at Ferranti's Wythenshawe Automation Division, Manchester, by Maurice Gribble. The starting point was a prototype digital computer developed for the Blue Envoy guided missile using low power hearing aid transistors. Announced by Ferranti as the 'process control transistor computer' in November 1958, Argus came into civilian and military use in 1962. It was used for process control at a soda ash plant for ICI and as part of a Cold War missile guidance system for the Bloodhound Mark 2 surface-to-air missile deployed by the Royal Air Force. While a small team of engineers within Ferranti used Argus to develop digital techniques for guided missile control, another technically powerful group of civilian users led development of the Argus for direct digital control of an ICI chemical plant at Fleetwood, Lancashire. The paper shows how the computer was invented, how it was developed in military and civilian contexts by small communities of practice and how these groups coalesced, grew and dispersed. As projects shifted towards software development, teams became smaller and women programmers were given considerable responsibility. These events highlight a key transition from analogue to digital control in manufacturing industry and defence during the early 1960s. Use of direct digital control by ICI followed commercial logic. The military were forced to switch to digital computation because technical advances in radar meant analogue calculations would not be accurate enough for Bloodhound Mark 2.